P-EP028. Low-dose perampanel improves refractory cortical myoclonus by the dispersed and suppressed paroxysmal depolarization shifts in the sensorimotor cortex. Issue 8 (August 2021) - Oi, Kazuki; Neshige, Shuichiro; Hitomi, Takefumi; Kobayashi, Katsuya; Tojima, Maya; Matsuhashi, Masao; Shimotake, Akihiro; Fujii, Daiki; Matsumoto, Riki; Kasama, Shuhei; Kanda, Masutaro; Wada, Yoshiaki; et al.
Abstract : Introduction. Although low-dose perampanel (PER) is reportedly effective on cortical myoclonus in a limited number of patients, its underlying mechanisms remain unclear. We aimed to extract and elaborate the clinical effects of PER on refractory cortical myoclonus for dose, etiology and also somatosensory-evoked potential (SEP) findings. Method. We examined 18 epilepsy patients with seizure and cortical myoclonus (10 males; mean age, 48.4 ± 16.2 years; Unverricht-Lundborg disease = 7, benign adult familial myoclonus epilepsy = 6, dentatorubral-pallidoluysian atrophy = 2, Gaucher disease = 1, and Lance-Adams syndrome = 2). Based on data accumulated before and after PER treatment, activities of daily life [ADL]), short latency, cortical components of SEP, and PER blood concentration were analyzed. Results. PER (mean dose: 3.2 ± 2.1 mg/day) significantly improved seizure frequency, myoclonus and ADL scores. It also significantly decreased the amplitude of and prolonged correlate with clinical scores among all patients. In contrast, the degree of P25 prolongation ms) significantly correlated with improved ADL score (p = 0.019) and blood PER concentration (p = 0.011). The degree of N33 prolongation (32.1 ± 4.0 to 33.7 ± 3.4 ms) was positively correlated with ADL score and blood PER concentration (p = 0.025 and p = 0.025, respectively). Conclusion. Low-dose PER markedly improved myoclonus and ADL in patients with refractory cortical myoclonus. SEP, especially P25 latency, is a potentially good biomarker to assess the objective effects of PER on intractable cortical myoclonus. (https://doi.org/10.1016/j.clinph.2019.07.006 ).